Depositional environment of Middle Triassic organic‐rich shales in the Ordos Basin, Northwest China. (21st July 2021) - Zhao, Xiangdong; Wang, Wei; Xie, Guwei; Pan, Songqi; Jarzembowski, Edmund A.; Zheng, Daran
Abstract : The Middle Triassic Tongchuan Formation in the Ordos Basin of northwestern China is a typical lacustrine deposit. A major component of this formation is thick layers of organic‐rich shales that are probably a potential hydrocarbon source and preserve the earliest known Mesozoic‐type lacustrine ecosystem. The exact depositional environment of the shales in the Tongchuan Formation, however, remains unknown. To address this question, we carried out high‐resolution carbon (δ 13 Corg ) and sulphur (δ 34 Spy ) isotope analysis as well as undertook total organic carbon (TOC)/pyrite contents and pyrite morphology investigation, and framboidal pyrite size measurements in shales of the Bawangzhuang section of the southern Ordos Basin. Remarkably high TOC (23 ± 9%) and pyrite (7 ± 3%) contents were obtained from the shales, which indicate a large amount of organic carbon and pyrite burial during shale deposition. Framboids are the dominant pyrite morphology in the pyrite crystals and show large and variable mean diameters (7.0 ± 1.7 μm to 14.3 ± 6.8 μm) across the section, indicating oxic–dysoxic bottom water during shale deposition. δ 13 Corg and δ 34 Spy revealed narrow and less variable values, ranging from −31.8‰ to −28.1‰, and −4.1‰ to 4.9‰, respectively. The δ 13 Corg values suggest balanced and consistent carbon cycles. Integrated with pyrite content and morphological patterns, consistent δ 34 Spy values probably demonstrate a relatively open environment for the formation of sedimentary pyrite, and thus a shallow chemocline that was quite close to the water‐to‐sediment interface during shale deposition. Overall, the organic‐rich shales of the Tongchuan Formation were probably deposited under oxic–dysoxic bottom‐water conditions. Shallow chemocline depth combined with moderately high sedimentation rate and high primary productivity may have played crucial roles in the deposition and formation of the organic‐rich shales in the Tongchuan Formation. The shallow chemocline also facilitates the fossil preservation in a lacustrine environment. Abstract : Geochemical profiles of the Bawangzhuang section in the Ordos Basin, indicating oxic‐dysoxic bottom water environment but with shallow chemocline during shale deposition